Cyanidin chloride modestly protects Caco-2 cells from ZnO nanoparticle exposure probably through the induction of autophagy. (May 2019) - Jiang, Leying; Li, Zhen; Xie, Yixi; Liu, Liangliang; Cao, Yi
Abstract: Recent studies suggest that phytochemicals, as part of the food matrix, might alter the toxicity of nanoparticles (NPs); however, relatively few studies have investigated the impact of anthocyanidins on the toxicity of NPs to cells lining the gastrointestinal tract. Therefore, this study used cyanidin chloride (CC) as the model for anthocyanidins and investigated the effects of CC on the toxicity of ZnO or Ag NPs to Caco-2 cells. Exposure to ZnO but not Ag NPs significantly induced cytotoxicity. The presence of CC, but not its analog quercetin (Qu), modestly protected Caco-2 cells from ZnO NP exposure. However, the intracellular superoxide, Zn ions, or release of interleukin-8 after ZnO NP exposure were not significantly affected by the presence of CC. Rather, CC promoted the expression of autophagic genes ATG5, ATG7, and BECN1 as well as the ratio of LC3-II/I after exposure to ZnO NPs. Meanwhile, the presence of autophagic inhibitors (chloroquine, NH4 Cl, bafilomycin A1) significantly promoted the cytotoxicity of ZnO NPs and inhibited the cytoprotective effects of CC. In conclusion, these data suggest that CC could modestly protect Caco-2 cells from ZnO NP exposure, probably through the induction of autophagy. Graphical abstract: Image 1 Highlights: ZnO but not Ag NPs significantly induced cytotoxicity to Caco-2 cells. Cyanidin chloride (CC)/quercetin (Qu) had minimal impact on colloidal properties of ZnO/Ag NPs. CC but not Qu modestly protected Caco-2 cells from ZnO NP exposure. ZnO NP-induced intracellular superoxide, Zn ions and IL-8 release were not affected CC. CC promoted autophagy activity, which may be responsible for the cytoprotective effects.